A two-step method to evaluate the Well-To-Wheel carbon efficiency of Urban Consolidation Centres. (October 2017) - Nocera, Silvio; Cavallaro, Federico
Abstract: With 25% of CO2 transport-related emissions, urban freight mobility is a relevant cause of climate change. Its optimization is a main aim of the Sustainable Urban Logistic Plans. Currently, the CO2 analysis of such plans is mostly based on a Tank-To-Wheel approach, which does not consider fuel production and distribution, thus not providing a comprehensive evaluation of its carbon effects. In this paper, we propose an alternative two-step approach: after quantifying CO2 emissions through a Well-To-Wheel methodology, which assesses the entire energy pathway of the fuel, we valuate them economically, using a meta-analysis of 700 studies. We test this model to assess the carbon potentialities of a new Urban Consolidation Centre (UCC) in the city of Lucca, Italy. Our results indicate a potential yearly saving of up to 190 tCO2 (which corresponds to about €10, 000 of social cost savings). These benefits are mostly obtained through third funds, which make the investment financially sustainable for the municipality. With adequate adaptations, the model can be used in other urban areas to assess the carbon potentiality of different transport measures. Furthermore, an integration of the long-distance freight movement can provide the total CO2 contribution of freight transport.